Optimizing Investment Strategies with the Reconfigurable Hardware Platform RIVYERA. (10th April 2012) - Starke, Christoph; Grossmann, Vasco; Wienbrandt, Lars; Koschnicke, Sven; Carstens, John; Schimmler, Manfred
Abstract : The hardware structure of a processing element used for optimization of an investment strategy for financial markets is presented. It is shown how this processing element can be multiply implemented on the massively parallel FPGA-machine RIVYERA. This leads to a speedup of a factor of about 17, 000 in comparison to one single high-performance PC, while saving more than 99% of the consumed energy. Furthermore, it is shown for a special security and different time periods that the optimized investment strategy delivers an outperformance between 2 and 14 percent in relation to a buy and hold strategy.